Logical Semantics in the “Stories for Rainy Days” by Naela Ali - Rada Mayasari; Masdiana Lubis; Dian Marisha Putri (LingPoet: Journal of Linguistics and Literary Research, 2021)
This research aims to analyze the elaboration, extension, and improvement contained in the data. The data source of this research is Naela Ali’s story of rainy days written by Naela Ali as the best-selling short story in 2018. The research data is in the form of clauses collected from short stories on rainy days. The theory used to analyze the meaning of the data is a logical-semantic theory. From this study, There are 3 types of logical semantic found in “Stories for Rainy Days” Short Story By Naela Ali: elaboration, extension, and enhancement. this research concludes that there is 83 logical semantics (expansion) found in the "stories for rainy days" consisting of 5 elaborations; 65 paratactic extensions and 1 hypotactic extension; 1 increased paratactic and 9 increased hypotactic; and 2 extensions and enhancements. The realization of logical semantic relation used in “Stories for Rainy Days” Short Story By Naela Ali based on the kinds of each logical-semantics those are: Elaboration consist of exemplification and clarification, there is no exposition. Extension consists of addition, variation, alternation. Enhancement consists of paratactic enhancement and hypotactic enhancement including manner, causal-purpose, spatial and causal-reason.